2022
DOI: 10.3390/nu14224797
|View full text |Cite
|
Sign up to set email alerts
|

A Choice Experiment Model for Honey Attributes: Italian Consumer Preferences and Socio-Demographic Profiles

Abstract: Honey production is currently experiencing a great deal of media attention, with many positive attributes of this hive product emerging. The purpose of the study is to investigate consumer preference and what key information informs people’s purchase of honey. This study is based on consumer surveys and experimental evaluation. First of all, the relative importance assigned by consumers to 12 honey product attributes was defined by using the best–worst scaling (BWS) methodology. Secondly, the latent class anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The characterisation of the physicochemical and biological properties of honey samples from areas with a high floral diversity and endemicity is highly attractive for beekeepers, consumers as well as the pharmaceutical industry. Honey consumer behaviour, partially due to the Covid-19 pandemic, is increasingly associated with honey health benefits and the presence of organoleptic compounds [ 38 ]. The most common biological properties that consumers are aware of in honey are its natural antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…The characterisation of the physicochemical and biological properties of honey samples from areas with a high floral diversity and endemicity is highly attractive for beekeepers, consumers as well as the pharmaceutical industry. Honey consumer behaviour, partially due to the Covid-19 pandemic, is increasingly associated with honey health benefits and the presence of organoleptic compounds [ 38 ]. The most common biological properties that consumers are aware of in honey are its natural antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a research investigation into the purchasing preferences of strawberries among German consumers by Bhat et al [14] revealed a rising awareness of the health benefits associated with the consumption of strawberries. This awareness is aligned with a wider trend of increased attention to the nutritional qualities of regularly consumed food [69,72,73].…”
Section: Discussionmentioning
confidence: 91%
“…The results show that Generations Y and Z have low awareness about creamed honey and honey with additions, which could be justified by the fact that younger consumers are indifferent towards honey in general [70]. In the context of the above, Sparacino et al [71] add that flavour is a very important attribute for the consumption of honey. Mateescu et al [72] state that a flavoured creamed honey is a good choice for consumers who are interested in consuming a spreadable product with an original flavour and nutritional benefits.…”
Section: Discussionmentioning
confidence: 95%